1998
DOI: 10.1046/j.1525-1497.1998.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for problem drinking

Abstract: OBJECTIVE:To assess the effect of a screen for problem drinking on medical residents and their patients. DESIGN:Descriptive cohort study. SETTING: Veterans Affairs Medical Clinic.PATIENTS: Patients were screened 2 weeks before a scheduled visit ( n ‫؍‬ 714). Physicians were informed if their patients scored positive. MEASUREMENTS AND MAIN RESULTS:Physician discussion of alcohol use was documented through patient interview and chart review. Self-reported alcohol consumption was recorded. Of 236 current drinkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Sensitivity, specificity, and positive and negative predictive values [ 21 ] of each score on the AUDIT-C and AUDIT-3 were calculated, relative to cutoff scores on the 10-item AUDIT, as follows: at-risk drinkers (score ≥ 8); high-risk drinkers (score ≥ 13); and likely dependent drinkers (score ≥ 20) [ 5 , 8 , 11 ]. For this study, sensitivity is the proportion of respondents identified as problem drinkers on the 10-item AUDIT who are also identified as problem drinkers on AUDIT-C and/or AUDIT-3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity, specificity, and positive and negative predictive values [ 21 ] of each score on the AUDIT-C and AUDIT-3 were calculated, relative to cutoff scores on the 10-item AUDIT, as follows: at-risk drinkers (score ≥ 8); high-risk drinkers (score ≥ 13); and likely dependent drinkers (score ≥ 20) [ 5 , 8 , 11 ]. For this study, sensitivity is the proportion of respondents identified as problem drinkers on the 10-item AUDIT who are also identified as problem drinkers on AUDIT-C and/or AUDIT-3.…”
Section: Methodsmentioning
confidence: 99%
“…Screening Aboriginal people to assess their level of alcohol consumption is recognized as an important initial step for determining their risk of alcohol-related harm and the need for alcohol intervention [ 4 - 6 ]. Alcohol screening can also be effective for engaging Aboriginal patients in discussions about their drinking [ 7 ] and can result in reduced alcohol consumption, independent of intervention [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that problem drinkers (hazardous drinking, alcohol abuse and alcohol dependence) can benefit from physician intervention [6], but lack of recognition of alcohol related problems by primary health care workers has been frequently reported [7,8]. Detection of alcohol abuse is particularly challenging in the busy out-patient and emergency departments.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use will be assessed with the Alcohol Use Disorder Identification Test (AUDIT) [61], a screening questionnaire for alcohol-related problems in the past year. Current smoking and physical activity will be assessed by two single questions from NEMESIS on current smoking and number of hours per week spent in physical exercise or sport lately, not counting sedentary pursuits such as chess or fishing [60].…”
Section: Methodsmentioning
confidence: 99%